Analisis Kinerja Keuangan Bank Umum Syariah (BUS) melalui Pendekatan Islamicity Perfomance Index - Dewi Sjam; Clarashinta Canggih (Jurnal Ilmiah Ekonomi Islam, 2022)
The study aims to analyze the financial performance of Sharia commercial banks in Indonesia during 2016-2020 using the Islamicity Perfomance Index (IPI) approach. Measured by Profit Sharing Ratio, Zakat Perfomance Ratio, Equitable Distribution Ratio, Directors-Employee Welfare Ratio, and Islamic Income vs Non Islamic Income. In particular, these index not only measure materially, but also measures the social responsibility of Islamic banking performance. Data analysis used quantitative descriptive method. The research sample taken was 11 (eleven) Islamic banks and considered related to data, period, registered on the Financial Service Authority (OJK). The data obtained from annual report through the Islamic Bank official website. From the study result, it can be concluded that financial perfomance at Sharia Commercial Banks has not had a positive increase along the years. There was a significant degradation on 2017. It is affected by the value of zakat distribution and shareholders. But in terms of halalness, Sharia commercial banks have avoided the element of usury.